On business & economics - Kuyper, Abraham, 1837-1920.; Heslam, Peter S. (Peter Somers) (Bellingham, WA : Lexham Press, 2021)
In this anthology of essays, speeches, and relections, we see Kuyper's attempts to think positively and creatively about th ecalling and potential of business. Included are his ideas about economic freedom, the eternal value of earthly work, stewardship and philanthropy, economic globalization, the workings of God's grace in business, and the social function of money. From dust jacket.
Includes bibliographical references (p. 399-410) and index.
Keywords: Kuyper, Abraham, -- 1837-1920.; Business -- Religious aspects -- Reformed Church; Economics -- Religious aspects -- Reformed Church; Business ethics; Economics -- Moral and ethical aspects